Recent Advances in Basic Research for CSF1R-Microglial Encephalopathy - Wang, Yan-Li; Wang, Fang-Ze; Li, Runzhi; Jiang, Jiwei; Liu, Xiangrong; Xu, Jun (Frontiers in Aging Neuroscience, 2021)
Colony-stimulating factor-1 receptor-microglial encephalopathy is a rare rapidly progressive dementia resulting from colony-stimulating factor-1 receptor (CSF1R) mutations, also named pigmentary orthochromatic leukodystrophy (POLD), hereditary diffuse leukoencephalopathy with spheroids (HDLS), adult-onset leukoencephalopathy with axonal spheroids, and pigmented glia (ALSP) and CSF1R-related leukoencephalopathy. CSF1R is primarily expressed in microglia and mutations normally directly lead to changes in microglial number and function. Many animal models have been constructed to explore pathogenic mechanisms and potential therapeutic strategies, including zebrafish, mice, and rat models which are with CSF1R monogenic mutation, biallelic or tri-allelic deletion, or CSF1R-null. Although there is no cure for patients with CSF1R-microglial encephalopathy, microglial replacement therapy has become a topical research area. This review summarizes CSF1R-related pathogenetic mutation sites and mechanisms, especially the feasibility of the microglia-original immunotherapy.